Retirement on the different government agencies in Leyte - Abayon, Ynah Camille; Castanares, Harlene; Centino, Toni Grace; Mercado, Cyril; Sarmen, Sapphire Kein; Exconde, Amy Joan E. (2016)
Retirement is one of the most important life events an individual will experience. Realizing a comfortable retirement requires a sensible preparation and a good planning. It is a continuous responsibility that should be managed well for an individual to achieve a fulfilling retirement years. Moreover, one's retirement is affected by different factors, management-and self-initiated variables, hence a strong involvement between the management where an individual work and the employee itself in planning for his or her retirement is strongly recommended.
Undergraduate research (Bachelor of Science in Management) -- University of the Philippines, Tacloban.
Keywords: Retirement